TGF-β and IL-12 conversely orchestrate the formation of CD103+ CD8 tumor-resident memory T cells to regulate response to therapeutic cancer vaccine - Stéphanie Corgnac; Isabelle Damei; Chiara Gentile; Aziza Caidi; Séverine Badel; Mélanie Phayanouvong; Fathia Mami-Chouaib (iScience, 2025)
Summary: The accumulation of CD103+ CD8 tumor-resident memory T (TRM) cells is predictive of response to cancer immunotherapy. Here, we show that a therapeutic peptide vaccine controls tumor growth in wild-type mice, but not in CD103-knockout mice. CD8 tumor-infiltrating T lymphocytes include two major TRM subpopulations expressing either CD49a or CD103 integrin, with a subset co-expressing CD103 and Tcf-1. Vaccination induces a decrease in the percentage of Tcf-1+CD103+ TRM-like cells and expansion of CD49a+ TRM displaying an effector/exhausted profile. Tcf-1+CD103+ TRM-cell density increases in tumors from transgenic mice constitutively expressing active TGF-β-type-2-receptor and wild-type mice challenged with neutralizing anti-IL-12 antibodies. The stimulation of CD8 T cells with recombinant (r)TGF-β combined with anti-CD3 antibodies results in an increase in the proportion of Tcf-1+CD103+ cells, whereas rIL-12 decreases CD103 expression. These results highlight the opposite effects of TGF-β and IL-12 in the regulation of TRM-cell development and suggest that targeting Tcf-1+CD103+ CD8 TRM may improve immunotherapy efficacy.